Penerapan Sistem Enterprise Resource Planning (ERP) Pada Sektor UMKM - Azizah, Maulidya Nanda; Setianti, Diva Istighfarin Ayu; Nugroho, Aryo (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
Small Micro Mediaum Enterprises, or MSME, are profitable companies owned by people, organizations and other business entities that fit the definition of a micro enterprise. MSME often do not apply information systems technology or even consider using it. In the UMKM DJS Shop (Dodolan Jajan Surabaya), in carrying out its business processes it still uses traditional methods, which require manual processes. Records of purchases, sales and product storage that have not been properly integrated, spend a lot of time and effort. In this research, a web-based ERP information system is designed and implemented to solve existing problems. The prototype method is used in this research. In the process of designing this system using UML, and implementing the system using open-source Odoo. The study’s output output is an ERP information system with modules for sales, inventory, and purchase that can solve issues with DJS Store. Blackbox testing findings demonstrate that the module configuration satisfies user requirements and operates as intended.